From university to secondary education: didactic strategies for teaching medieval and early modern history with a gender-inclusive approach (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2026)
Bridging the gap between knowledge production in the university setting and other levels of education remains an ongoing challenge. Even more pressing is the need to ensure the inclusion of approaches proposed by Comprehensive Sexual Education (ESI) in addressing different historical processes from a gender perspective. This article presents the experience developed over the past ten years by the History of Europe II course at the Faculty of Humanities and Arts of the University of Rosario. The initiative has sought to bring these new ways of reconstructing the past closer to university students and to teachers working in secondary education in the province of Santa Fe.
Keywords: gender; medieval history; didactic transposition